Negative electrode sheet and lithium ion secondary battery

By designing an active layer with high infrared absorption in the negative electrode sheet of the lithium-ion battery, the problem of poor discharge performance of lithium-ion batteries in the low temperature environment is solved, and better low temperature discharge capacity is achieved.

CN119786520APending Publication Date: 2025-04-08ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411995281.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The poor discharge performance of lithium-ion batteries in low temperature environments is mainly due to the increase in electrolyte viscosity, reduced conductivity and slowing down the diffusion rate of lithium ions in positive and negative electrode materials.

Method used

A negative electrode sheet is designed, including a negative electrode current collector and a negative electrode active layer arranged on at least one side surface in the thickness direction of the negative electrode current collector. The negative electrode active layer consists of adjacent first active layer and second active layer, and the first active layer has a higher infrared absorption rate to improve the insulation effect.

Benefits of technology

By improving the insulation effect of the negative electrode sheet, the low-temperature discharge capacity of lithium-ion batteries is significantly improved, ensuring that the battery can still discharge effectively under extreme cold conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786520A_ABST
    Figure CN119786520A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of lithium-ion batteries, and discloses a negative electrode sheet and a lithium-ion secondary battery. The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one side of the surface of the negative electrode current collector. In a first direction, the negative electrode active layer includes adjacent first active layers and second active layers, and the second active layer is located at one end or both ends of the first active layer in the first direction; the first active layer is at 4000-2000cm ‑1 The infrared absorption rate A1 in the range of 4000-2000cm ‑1 The infrared absorption rate A2 within the range satisfies: 1.25≤A1 / A2≤2.25, and 75%≤A1≤90%. As a result, the first active layer has a higher ability to absorb thermal radiation than the second active layer, thereby being able to retain more heat, improving the thermal insulation effect of the first active layer, and effectively improving the low-temperature discharge capability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a negative electrode sheet and a lithium-ion secondary battery. Background Art

[0002] In the field of lithium-ion battery technology, poor discharge performance in low-temperature environments has always been one of the key factors restricting its application scope. Especially under extremely cold conditions, the discharge capacity and discharge efficiency of lithium-ion batteries will drop significantly, which is mainly due to the increase in electrolyte viscosity, decrease in conductivity, and slow diffusion rate of lithium ions in positive and negative electrode materials caused by low temperature environments.

[0003] To solve this problem, researchers are constantly exploring various methods to improve the low-temperature discharge performance of lithium-ion batteries. Currently, the commonly used methods to improve the low-temperature performance of lithium-ion batteries mainly focus on optimizing the electrolyte formulation, improving the positive and negative electrode materials, and designing more efficient thermal management systems. However, these methods often involve complex material synthesis and processing processes, and are costly, making them difficult to be widely promoted in practical applications. Summary of the invention

[0004] In view of this, the present application provides a negative electrode sheet and a lithium-ion secondary battery, which aim to solve the problem of poor low-temperature discharge performance of existing lithium-ion secondary batteries to a certain extent.

[0005] According to an embodiment of the present application, in a first aspect, a negative electrode sheet is provided, comprising a negative electrode current collector and a negative electrode active layer disposed on at least one side surface of the negative electrode current collector in a thickness direction; in a first direction, the negative electrode active layer comprises adjacent first active layers and second active layers, and the second active layer is located at one end or both ends of the first active layer in the first direction;

[0006] The first active layer has a wavelength of 4000-2000 cm -1 The infrared absorption rate in the range of 4000-2000cm is recorded as A1, and the second active layer has an infrared absorption rate of 4000-2000cm -1 The infrared absorption rate within the range is recorded as A2, and A1 and A2 satisfy: 1.25≤A1 / A2≤2.25, and 75%≤A1≤90%.

[0007] In some optional embodiments, 40%≤A2≤60%.

[0008] In some optional embodiments, in the first direction, the width of the first active layer is W1, 50 mm ≤ W1 ≤ 160 mm; the width of the second active layer is W2, W1 and W2 satisfy: W2 = (1 / 6 - 1 / 3) * W1.

[0009] In some optional embodiments, the compaction density T1 of the first active layer and the compaction density T2 of the second active layer satisfy: T1 = (0.9-1) * T2, 1.4 g / cm 3 ≤T2≤1.6g / cm 3 .

[0010] In some optional embodiments, the negative electrode sheet includes a plurality of electrode tabs, and the plurality of electrode tabs are arranged in sequence along the length direction of the negative electrode sheet.

[0011] In some optional embodiments, the negative electrode sheet includes a first region and a second region, the first region includes the first active layer, and the second region includes the second active layer; the thermal resistance R1 of the first region and the thermal resistance R2 of the second region satisfy: 2≤R1 / R2≤5, and 0.1mK / W≤R1≤0.125mK / W, 0.025mK / W≤R2≤0.05mK / W.

[0012] In some optional embodiments, the first active layer includes a first graphite material, and the first graphite material satisfies: a graphitization degree ≥ 0.93, a porosity P1 of 10%-40%, a median particle size G1 of 7 μm-11 μm, and a specific surface area S1 of 3 m 2 / g-6m 2 / g.

[0013] In some optional embodiments, the second active layer includes a second graphite material, and the second graphite material satisfies: a graphitization degree ≥ 0.93, a porosity P2 of 1%-5%, a median particle size G2 of 7μm-11μm, and a specific surface area S2 of 1m 2 / g-2m 2 / g.

[0014] In some optional embodiments, the first coulombic efficiency η1 of the first active layer and the first coulombic efficiency η2 of the second active layer satisfy: H=η1 / η2, and 0.90≤H≤0.99, 85%≤η1≤91%, 92%≤η2≤94%.

[0015] According to an embodiment of the present application, in a second aspect, a lithium-ion secondary battery is provided, comprising a positive electrode sheet, the negative electrode sheet described in the first aspect, and an electrolyte.

[0016] In some optional embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer disposed on at least one side surface of the positive electrode current collector in the thickness direction, the positive electrode active layer includes a ternary material, the median particle size G3 of the ternary material is 2 μm-6 μm, and the chemical formula of the ternary material is LiNi x Co y Mnz O 2 , where x+y+z=1, 0.6≤x<1, 0<y<0.2, 0<z<0.2.

[0017] In some optional embodiments, the lithium ion solid phase diffusion coefficient D1 of the ternary material is 3×10 - 12 cm 2 / s-2.5×10 -10 cm 2 / s, the lithium ion solid phase diffusion coefficient D2 of the first graphite material is 4.0×10 -12 cm 2 / s-2.0×10 -9 cm 2 / s, and D1 and D2 satisfy: C = (lgD1) / (lgD2), 0.84≤C≤1.32.

[0018] In some optional embodiments, the electrolyte includes an organic solvent and an electrolyte and an additive dissolved in the organic solvent, the organic solvent includes ethylene carbonate, ethyl methyl carbonate and methyl acetate, and the content of methyl acetate is 15%-30% based on the mass of the electrolyte.

[0019] In some optional embodiments, the additive includes fluoroethylene carbonate and / or lithium difluorophosphate. Based on the mass of the electrolyte, the content of the fluoroethylene carbonate is 2%-10%, and the content of the lithium difluorophosphate is 0.5%-3.5%.

[0020] In some optional embodiments, based on the mass of the electrolyte, the content of the fluoroethylene carbonate is 3%-5%.

[0021] In some optional embodiments, based on the mass of the electrolyte, the content of the lithium difluorophosphate is 1%-2.5%.

[0022] The technical solution of this application has the following advantages:

[0023] The negative electrode active layer in the negative electrode sheet provided in the present application comprises a first active layer and a second active layer adjacent to each other in a first direction, wherein the second active layer is located at one or both ends of the first active layer in the first direction; the first active layer is at 4000-2000 cm -1 The infrared absorption rate A1 of the second active layer is in the range of 4000-2000cm -1The infrared absorption rate A2 within the range satisfies: 1.25≤A1 / A2≤2.25, and 75%≤A1≤90%. As a result, the first active layer has a higher ability to absorb thermal radiation than the second active layer, thereby being able to retain more heat, improving the thermal insulation effect of the first active layer, and effectively improving the low-temperature discharge capability of the battery.

[0024] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 It is a schematic diagram of the structure of a negative electrode sheet in one embodiment of the present application.

[0027] Figure 2 It is the SEM image of porous graphite.

[0028] Figure 3 It is a comparison chart of low-temperature discharge curves of Example 1 of the present application and Comparative Example 1.

[0029] The reference numerals are described as follows:

[0030] 1. First active layer; 2. Second active layer; 3. Tab. DETAILED DESCRIPTION

[0031] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0032] It should be noted that the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance. In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.

[0033] First of all, it should be noted that the edge area of ​​the negative electrode sheet has a larger current than the middle area due to the lead-out of the pole ear. According to Joule's law, the edge area generates more heat. Under low temperature conditions, the heat accumulation in the edge area of ​​the negative electrode sheet is enough to enable the battery to discharge, while the heat generated in the middle area of ​​the negative electrode sheet is less, and the heat generated is less than the heat dissipated by the battery to the environment. The battery Joule heat cannot be accumulated, thus restricting the discharge capacity of fast-charging lithium-ion batteries at low temperatures.

[0034] In order to solve the above problems existing in the related art, according to the first aspect of the present application, a negative electrode sheet is provided, and its structure is shown in Figure 1 , comprising a negative electrode current collector and a negative electrode active layer disposed on at least one side surface of the negative electrode current collector in the thickness direction; in a first direction, the negative electrode active layer comprises adjacent first active layers 1 and second active layers 2, and the second active layer 2 is located at one end or both ends of the first active layer 1 in the first direction; Figure 1 As shown, the first direction may be the width direction (Y direction) of the negative electrode sheet. In some other embodiments, the first direction may also be the length direction (X direction) of the negative electrode sheet.

[0035] The first active layer 1 has a wavelength of 4000-2000 cm -1 The infrared absorption rate in the range of 4000-2000cm is recorded as A1, and the second active layer 2 has an infrared absorption rate of 4000-2000cm -1 The infrared absorption rate within the range is recorded as A2, and A1 and A2 satisfy: 1.25≤A1 / A2≤2.25, and 75%≤A1≤90%.

[0036] As a result, the first active layer has a higher ability to absorb thermal radiation than the second active layer, so that it can retain more heat, improve the thermal insulation effect of the first active layer, and effectively improve the low-temperature discharge capacity of the battery. And when the infrared absorption rate A1 of the first active layer is in the range of 75%-90%, it can ensure that the negative electrode has excellent thermal insulation performance and low-temperature discharge capacity. The present application study found that if the infrared absorption rate of the first coating is too low, it will lead to insufficient ability to absorb thermal radiation, poor heat absorption and retention effects, reduce the thermal insulation performance of the negative electrode, and thus affect the low-temperature discharge capacity; and if the infrared absorption rate of the first coating is too high, it means that the first coating has too strong ability to absorb thermal radiation, absorbs and accumulates a large amount of heat energy that cannot be effectively dissipated, and under normal conditions will cause the internal temperature of the material to rise rapidly, affecting the battery life and safety.

[0037] It is understandable that infrared spectrometers have a wavelength range of 4000-2000cm -1The wave number range is usually relatively stable, and the wave number accuracy and resolution are relatively high. Therefore, this application only considers the infrared absorption rate of the active layer within the above wave number range. Exemplarily, the infrared absorption rate A1 of the first active layer can be 75%, 80%, 85%, 90%, etc. or within the range formed by any two of the above values, and the infrared absorption rate A2 of the second active layer can be 40%, 45%, 50%, 55%, 60%, etc. or within the range formed by any two of the above values. The value of A1 / A2 can be, for example, 1.25, 1.5, 1.75, 2.0, 2.25, etc. or within the range formed by any two of the above values.

[0038] It is understandable that the coating width of the first active layer will affect the thermal insulation effect of the negative electrode sheet. The larger the coating width, the better the thermal insulation effect at the same coating thickness. Figure 1 , in the width direction (Y direction) of the negative electrode sheet, the width of the first active layer 1 is W1, 50mm≤W1≤160mm; the width of the second active layer 2 is W2, W1 and W2 satisfy: W2=(1 / 6-1 / 3)*W1, thereby further improving the low-temperature discharge performance of the battery. This application study found that if the value of W1 / W2 is too small, the thermal insulation effect of the first coating is not obvious enough to support the discharge of the battery at low temperatures, and if the value of W1 / W2 is too large, it means that the coating width of the first coating is too wide, which will cause inconsistent heat accumulation at the junction of the first coating and the second coating under the current effect, and the internal stress cannot be balanced, resulting in cracks at the junction during the process of lithium insertion and extraction, which will cause the battery to bulge during the cycle, affecting the battery life and safety.

[0039] Exemplarily, the width W1 of the first active layer can be 50 μm, 70 μm, 90 μm, 100 μm, 120 μm, 140 μm, 160 μm, etc., or can be within the range of any two of the above values, and the value of W1 / W2 can be, for example, 3, 3.5, 4, 4.5, 5, 5.5, 6, etc., or can be within the range of any two of the above values.

[0040] In some embodiments, the negative electrode sheet includes a first region and a second region, the first region includes the first active layer 1, and the second region includes the second active layer 2; that is, the orthographic projection region of the first active layer in the negative electrode sheet along its thickness direction is defined as the first region, and the orthographic projection region of the second active layer in the negative electrode sheet along its thickness direction is defined as the second region. The thermal resistance R1 of the first region and the thermal resistance R2 of the second region satisfy: 2≤R1 / R2≤5, and 0.1mK / W≤R1≤0.125mK / W, 0.025mK / W≤R2≤0.05mK / W.

[0041] The thermal resistance value of the negative electrode sheet reflects its heat preservation ability. The larger the thermal resistance, the stronger the heat preservation ability. By making the thermal resistance value of the first area greater than the thermal resistance value of the second area, it can be ensured that the first area has better heat preservation ability than the second area, so that when the battery is discharged in a low temperature environment, the heat generated inside the battery will not be quickly dissipated into the environment, which can further improve the low temperature discharge performance of the battery. The present application found that if the value of R1 / R2 is too small, it means that the heat preservation ability of the first area is poor, resulting in the Joule heat generated by the discharge in the middle area of ​​the negative electrode sheet cannot support the normal discharge of the battery at low temperature. When the value of R1 / R2 is too large, the heat preservation ability of the middle area of ​​the negative electrode sheet is too good, so that the battery cannot effectively dissipate heat when used under normal temperature conditions, the overall temperature of the battery is too high, and the side reactions are significantly increased, resulting in a significant deterioration in the battery cycle performance.

[0042] Exemplarily, the thermal resistance R1 of the first region can be 0.1mK / W, 0.105mK / W, 0.11mK / W, 0.115mK / W, 0.12mK / W, 0.125mK / W, etc., or be within the range formed by any two of the above values. The thermal resistance R2 of the first region can be 0.025mK / W, 0.03mK / W, 0.035mK / W, 0.04mK / W, 0.045mK / W, 0.05mK / W, etc., or be within the range formed by any two of the above values. The value of R1 / R2 can be, for example, 2, 2.5, 3, 3.5, 4, 4.5, 5, etc., or be within the range formed by any two of the above values.

[0043] It can be understood that the negative electrode current collector extends and protrudes in the width direction of the negative electrode sheet to form a plurality of tabs 3, such as Figure 1 As shown, the plurality of tabs 3 are arranged in sequence along the length direction of the negative electrode sheet, for example, they can be arranged at equal intervals. This ensures that the battery has good rate performance and a small charge and discharge temperature rise, which is suitable for battery fast charging occasions.

[0044] In some specific embodiments, the first active layer includes a first graphite material, and the first graphite material satisfies: a graphitization degree ≥ 0.93, a porosity P1 of 10%-40%, a median particle size G1 of 7 μm-11 μm, and a specific surface area S1 of 3 m 2 / g-6m 2 / g; the second active layer includes a second graphite material, and the second graphite material satisfies: graphitization degree ≥ 0.93, porosity P2 is 1%-5%, median particle size G2 is 7μm-11μm, specific surface area S2 is 1m 2 / g-2m 2 / g.

[0045] Compared with the second active layer, the first active layer uses porous graphite (i.e., the first graphite material) with a larger specific surface area. The SEM image is shown in Figure 2 , which can ensure that the middle area of ​​the negative electrode sheet (i.e., the first area) has the aforementioned higher heat radiation absorption capacity and better heat preservation capacity, thereby significantly improving the low-temperature discharge performance of the battery. Exemplarily, the porosity P1 of the first graphite material can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc. or within the range of any two of the above values, and the specific surface area S1 of the first graphite material can be, for example, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g, 5.5m 2 / g, 6m 2 / g, etc. or within the range formed by any two of the above values.

[0046] Due to the porous characteristics of the first graphite material, the first coulombic efficiency of the first active layer is slightly lower than the first coulombic efficiency of the second active layer. In some embodiments, the first coulombic efficiency η1 of the first active layer satisfies 85%≤η1≤91%, and the first coulombic efficiency η2 of the second active layer satisfies 92%≤η1≤94%. As an example, the first coulombic efficiency η1 of the first active layer can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, etc., or within the range of any two of the above values, and the first coulombic efficiency η2 of the second active layer can be 92%, 92.5%, 93%, 93.5%, 94%, etc., or within the range of any two of the above values.

[0047] The difference in the first coulombic efficiency of the two active layers on the negative electrode sheet will lead to differences in the battery CB value. The CB value (Cell Balance) refers to the ratio of the negative electrode capacity to the positive electrode capacity at the same stage and under the same conditions. In battery design, in order to prevent lithium plating, it is usually required that the NP ratio (that is, the ratio of the negative electrode capacity to the positive electrode capacity) is greater than 1, that is, the negative electrode must be in excess.

[0048] In some embodiments of the present application, the first coulombic efficiency η1 of the first active layer and the first coulombic efficiency η2 of the second active layer satisfy: H = η1 / η2, 0.90≤H≤0.99. The negative electrode sheet designed in this way can not only ensure that the energy density of the battery is not lost, but also ensure that the battery has excellent cycle performance in a low temperature environment. Since the first coulombic efficiency of the first active layer in the middle area of ​​the negative electrode sheet is slightly lower, the number of reversible lithium ions in the middle area is less than that in the edge area, so that the NP ratio in the middle area is higher than that in the edge area. During the charging process, the porous graphite in the middle area is in a shallow charge and discharge state, and it is not easy to precipitate lithium even at low temperatures. Due to the large current and high heat generation in the edge area, the speed at which lithium ions are embedded in graphite is faster than that in the middle area, and lithium precipitation will not occur even if the NP is relatively small. In addition, the edge area of ​​the negative electrode sheet uses a second active layer with a higher first efficiency to ensure that the energy density of the battery is further improved.

[0049] Exemplarily, the value of H can be 0.90, 0.91, 0.93, 0.95, 0.97, 0.99, etc. or within the range formed by any two of the above values. The present application has found that if the H value is too small, it means that the first effect of the first active layer of porous graphite in the middle area of ​​the negative electrode sheet is too low, or the first effect of the second active layer of conventional graphite in the edge area is too high. If the first effect of the first active layer in the middle area of ​​the negative electrode sheet is too low, the gram capacity loss of the negative electrode material is too much, resulting in a significant decrease in the energy density of the battery. If the first effect of the second active layer in the edge area of ​​the negative electrode sheet is too high, the NP ratio in the edge area will be too low, which will cause lithium deposition when the battery is charged under low temperature conditions, causing battery safety problems. If the value of H is too large, it means that the first active layer in the middle area of ​​the negative electrode sheet and the second active layer in the edge area have the same initial effect. At this time, the porous graphite in the middle area is no longer in a shallow charge and discharge state. Due to the structural characteristics of the porous graphite, deep charge and discharge under low temperature conditions will cause the porous material structure to collapse, causing the battery capacity to decay faster. In severe cases, it may cause safety problems such as internal short circuits in the battery.

[0050] Due to the presence of the porous structure of the first graphite material, the thickness of the first paste layer after coating is significantly greater than the thickness of the second paste layer using conventional graphite. It can be understood that the active layer is obtained after the paste layer is dried and rolled. Therefore, in some embodiments of the present application, the compaction density T1 of the first active layer and the compaction density T2 of the second active layer satisfy: T1 = (0.9-1) * T2, 1.4 g / cm 3 ≤T2≤1.6g / cm 3. As a result, the negative electrode sheet after rolling has basically the same thickness as a whole, ensuring the flatness of the battery, which is beneficial to the battery's cycle performance. In addition, it can also ensure that the negative electrode sheet as a whole has a high stability. This is because the stress at the junction of the edge area and the middle area of ​​the negative electrode sheet is difficult to release during the cycle. The presence of three-dimensional pores in porous graphite helps to resist the stress generated during the charging and discharging process, preventing the negative electrode sheet from deforming or breaking and falling off, thereby extending the service life of the battery.

[0051] As an example, the ratio of the compaction density T1 of the first active layer to the compaction density T2 of the second active layer may be, for example, 0.9, 0.92, 0.94, 0.96, 0.98, 1.0, etc., or within the range of any two of the above values. The compaction density T2 of the second active layer may be 1.4 g / cm 3 , 1.45g / cm 3 , 1.5g / cm 3 , 1.55g / cm 3 , 1.6g / cm 3 or within the range formed by any two of the above values.

[0052] According to the second aspect of the present application, a lithium ion secondary battery is provided, comprising a positive electrode sheet, the negative electrode sheet described in the first aspect, and an electrolyte. The lithium ion secondary battery of the present application has good low temperature discharge performance, and further has high energy density, excellent cycle and safety performance.

[0053] It can be understood that the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer disposed on at least one side surface of the positive electrode current collector in the thickness direction, the positive electrode active layer includes a ternary material, the median particle size G3 of the ternary material is 2 μm-6 μm, and the chemical formula of the ternary material is LiNi x Co y Mn z O 2 , where x+y+z=1, 0.6≤x<1, 0<y<0.2, 0<z<0.2. Using small particle ternary materials as positive electrode active materials can effectively shorten the migration path of lithium ions in the positive electrode active materials, reduce the ion migration resistance, and thus improve the charge and discharge efficiency of the battery.

[0054] In some embodiments, the lithium ion solid phase diffusion coefficient D1 of the ternary material is 3×10 -12 cm 2 / s-2.5×10 -10 cm 2 / s, the lithium ion solid phase diffusion coefficient D2 of the first graphite material is 4.0×10 -12 cm 2 / s-2.0×10 - 9 cm 2 / s, and D1 and D2 satisfy: C = (lgD1) / (lgD2), 0.84 ≤ C ≤ 1.32. Such a design can minimize the migration barrier of ions in the electrode material, so that the lithium ion embedding speed on the positive electrode side and the lithium ion extraction speed on the negative electrode side are well matched, avoiding excessive accumulation of ions on either electrode side, thereby effectively improving low-temperature discharge performance.

[0055] Exemplarily, the value of C can be 0.84, 0.94, 1.04, 1.14, 1.24, 1.32, etc. or within the range formed by any two of the above values. The present application has found that if the value of C is too large, the lithium ion release rate on the negative electrode side is too slow, and there is no extra lithium ion reception on the positive electrode side, resulting in a large accumulation of electrons on the positive electrode side, an increase in the potential difference, and a significant deterioration in low-temperature discharge; and when the value of C is too small, the lithium ion embedding rate on the positive electrode side is too slow, and the lithium ions released from the negative electrode side are gathered in the electrolyte, the electrolyte concentration difference increases, resulting in an increase in internal resistance, and an aggravation of the polarization phenomenon during the discharge process, which also affects the low-temperature discharge performance of the battery.

[0056] The composition of the electrolyte will also have an important impact on the low-temperature performance of the battery. Generally, the electrolyte includes an organic solvent and an electrolyte and an additive dissolved in the organic solvent. In some embodiments of the present application, the organic solvent includes ethylene carbonate (EC), ethyl methyl carbonate (EMC) and methyl acetate (MA). Based on the mass of the electrolyte, the content of methyl acetate is 15%-30%. Exemplarily, the content of MA in the electrolyte can be 15%, 18%, 22%, 26%, 30%, etc. or within the range of any two of the above values. The combination of EC / EMC itself can provide higher ionic conductivity, which is conducive to low-temperature discharge. At the same time, the addition of MA can further reduce the viscosity of the electrolyte and improve the conductivity of the electrolyte, thereby significantly improving the low-temperature discharge performance of the battery. However, the addition of MA is not the more the better. The present application found that too much MA will increase high-temperature gas production, resulting in an increase in the cycle expansion rate.

[0057] In some embodiments, the additive includes fluoroethylene carbonate (FEC) and / or lithium difluorophosphate (LiPO 2 F 2), based on the mass of the electrolyte, the content of the fluoroethylene carbonate is 2%-10%, and the content of the lithium difluorophosphate is 0.5%-3.5%. Exemplarily, the content of FEC in the electrolyte can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., or within the range of any two of the above values, and the content of lithium difluorophosphate can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc., or within the range of any two of the above values.

[0058] This application study found that adding FEC and / or lithium difluorophosphate to the electrolyte can form a SEI film with a higher inorganic content, more stable structure, thinner thickness and uniformity, which helps to reduce the negative electrode interface impedance and promote the rapid diffusion and deintercalation of lithium ions, thereby improving the low-temperature discharge performance of the battery. If the content of the additive is insufficient, the battery life will decrease during normal cycles, and when the content of the additive is too high, the battery gas production problem will be aggravated, causing the battery cycle life to decay.

[0059] It is understood that the existing electrolytes that can be used for lithium-ion battery electrolytes can be applied to the present application, including but not limited to: lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium hexafluoroantimonate (LiSbF 6 ), lithium difluorophosphate (LiPF 2 O 2 )、4,5-dicyano-2-trifluoromethylimidazolium lithium (LiDTI), lithium bis(oxalate borate) (LiBOB), lithium difluorooxalate borate (LiDFOB), lithium bis(fluorosulfonyl)imide (LiFSI), lithium nitrate (LiNO 3 )、LiN(SO 2 RF) 2 、LiN(SO 2 F)(SO 2 RF) or a combination of the above, wherein RF = C n F 2n+1 , n is an integer from 1 to 10.

[0060] The present application is described in further detail below in conjunction with specific examples, and these examples should not be construed as limiting the scope of protection claimed in the present application. Where specific experimental steps or conditions are not indicated in the examples and comparative examples, the operation or conditions of the conventional experimental steps described in the literature in this area can be carried out. Where the reagents or instruments used do not indicate the manufacturer, they are all conventional reagent products that can be obtained commercially. In all examples and comparative examples of the present application, the unit % represents the mass percentage content.

[0061] Preparation example:

[0062] 1. Preparation of porous graphite:

[0063] Mesophase asphalt was selected as the precursor material. Meanwhile, 6g of polyvinyl alcohol (PVA, molecular weight 30,000-50,000) and 15ml of acrylic acid (AAc) were prepared, which will participate in the reaction as a hydrophilic polymer and an organic compound, respectively. 1ml of glutaraldehyde (GA, 25w%, soluble in water) and 1.5ml of ethylene glycol dimethacrylate (EGDMA) were also required as crosslinking agents for PVA and AAc, and 1ml of potassium persulfate (KPS) (2w%, soluble in water) was used as a free radical initiator for the polymer crosslinking reaction.

[0064] 6 g of polyvinyl alcohol was dissolved in 52 ml of 1 M NaOH solution at 160°C for 10 minutes to ensure that PVA was fully dissolved. Then the solution was cooled to room temperature, and 15 ml of levulinic acid, 1 ml of GA, 1.5 ml of ethylene glycol biguanide and 1 ml of KPS solution were added in sequence, and stirred to mix well to form a gel solution.

[0065] 12g of mesophase pitch (MP) was placed in an autoclave and subjected to heat stabilization treatment in an air atmosphere. The treatment process usually includes heating from room temperature to a pre-foaming temperature of 320°C at a heating rate of 2°C / min and keeping the temperature for 4 hours to ensure the stability of MP. After the treatment is completed, the oxidatively stabilized MP is added to the previously prepared gel solution and stirred again to mix the MP and the gel solution thoroughly.

[0066] The resulting mixed solution was heat treated at 100°C for 12 hours to remove moisture and volatiles therein, and then dried at 160°C for 13 hours to obtain a dry hydrogel containing MP.

[0067] Next, the dried hydrogel containing MP is heated and carbonized in an argon atmosphere. Carbonization process: The temperature is raised from room temperature to a carbonization temperature of 1200°C at a heating rate of 2°C / min, and the temperature is kept for 2 hours. The porous graphite is prepared by the carbonization process. Finally, the obtained carbon foam is further subjected to high-temperature heat treatment in an argon atmosphere. The heat treatment process includes heating to 2700°C at a heating rate of 2°C / min, and keeping the temperature for 2 hours to prepare porous graphite.

[0068] Example 1

[0069] 1. Preparation of negative electrode sheet:

[0070] The porous graphite, conductive agent carbon black, binder sodium carboxymethyl cellulose and styrene-butadiene rubber obtained in the preparation example were added into deionized water in a mass ratio of 96:1.5:1:1.5, mixed and stirred, and evenly dispersed to obtain the first negative electrode slurry to be coated; wherein the graphitization degree of the porous graphite was 95%, the porosity P1 was 25%, the median particle size G1 was 9 μm, and the specific surface area S1 was 5 m 2 / g.

[0071] Conventional graphite, conductive agent carbon black, binder sodium carboxymethyl cellulose and styrene-butadiene rubber are added into deionized water in a mass ratio of 96:1.5:1:1.5, mixed and stirred, and evenly dispersed to obtain a second negative electrode slurry to be coated; wherein the conventional graphite has a graphitization degree of 95%, a porosity P2 of 3%, a median particle size G2 of 9 μm, and a specific surface area S2 of 1.5 m 2 / g.

[0072] The first negative electrode slurry is evenly coated on the middle area of ​​the 6μm thick copper foil current collector (W1=70μm), and the second negative electrode slurry is evenly coated on the edge areas on both sides of the copper foil (W2=15μm). After drying, the negative electrode sheets to be wound are obtained by rolling, slitting and sheeting.

[0073] 2. Preparation of positive electrode:

[0074] The high nickel ternary material LiNi 0.8 Co 0.1 Mn 0.1 O 2 (G3 is 4μm), conductive agent (carbon nanotubes: carbon black = 1:3, w / w), adhesive PVDF are uniformly mixed with solvent N-methylpyrrolidone (NMP) in a mass ratio of 96:2.4:1.6 to obtain the positive electrode slurry to be coated, and the positive electrode slurry is uniformly coated on a 10μm thick aluminum foil. After drying, it is rolled, slit, and sheeted to obtain the positive electrode sheet to be wound.

[0075] 3. Production of finished batteries:

[0076] The positive and negative electrodes to be wound are prepared into lithium-ion batteries through winding, packaging, baking, injection, and formation. The electrolyte includes 31% EC, 31% EMC, 20% MA, 3% FEC, and 2% LiPO 2 F 2 and 13% LiPF 6 .

[0077] The preparation methods of Examples 2-14 and Comparative Examples 1-3 are basically the same as those of Example 1, and the differences are shown in Table 1. It should be noted that if the content of MA in the electrolyte increases, FEC, LiPO 2 F 2 and LiPF 6 The content of EC and EMC remains unchanged, while the content of EC and EMC is reduced at a mass ratio of 1:1, and vice versa.

[0078] In Table 1, P1 is the porosity of the first graphite material, S1 is the specific surface area of ​​the first graphite material, P2 is the porosity of the second graphite material, S2 is the specific surface area of ​​the second graphite material, W1 is the width of the first active layer, W2 is the width of the second active layer, T1 is the compaction density of the first active layer, and T2 is the compaction density of the second active layer.

[0079] In Table 2, G3 is the median particle size of the ternary material, D1 is the lithium ion solid phase diffusion coefficient of the ternary material, D2 is the lithium ion solid phase diffusion coefficient of the first graphite material, and C = (lgD1) / (lgD2). The values ​​of D1 and D2 are expressed in scientific notation.

[0080] Table 1

[0081]

[0082]

[0083] Table 2

[0084]

[0085]

[0086] Test Case

[0087] 1. Infrared absorption test

[0088] (1) Battery disassembly and negative electrode sheet acquisition: Safely disassemble the battery in a fully discharged (empty) state and remove the negative electrode sheet.

[0089] (2) Paste layer processing: Use a plastic scraper to gently scrape off the paste layer on the negative electrode sheet, collect the scraped paste layer, and prepare for subsequent processing.

[0090] (3) Ultrasonic treatment and filtration: The scraped paste layer was placed in a solvent, dimethyl carbonate (DMC), and the paste layer was subjected to ultrasonic treatment for 2 hours to wash away the organic SEI film and residual lithium salt.

[0091] (4) Pickling treatment: The cleaned negative electrode material is placed in a hydrochloric acid solution and soaked for 2 hours for pickling treatment. The purpose of pickling is to remove the inorganic SEI film on the negative electrode material.

[0092] (5) Cleaning and drying: Use deionized water to clean the negative electrode material after acid washing several times to completely remove the residual hydrochloric acid and other impurities. After cleaning, place the negative electrode material in a drying device for drying until it is completely dry.

[0093] (6) After mixing the sampled negative electrode material with potassium bromide (KBr) powder, press it into a transparent small disc using a tablet press. Place the prepared sample into the sample pool of the infrared spectrometer. Turn on the infrared spectrometer, preheat it to a stable state, and select 4000-2000cm according to the infrared absorption characteristics of the negative electrode sheet. -1 The wave number range is tested. Adjust the instrument parameters, such as scanning speed, resolution, etc., to obtain high-quality spectra. By analyzing the infrared absorption spectrum, the chemical bonds and functional groups in the negative electrode can be identified and their infrared absorption rates can be calculated.

[0094] 2. Thermal resistance test

[0095] Electrode sampling: put the battery into an empty state, disassemble the battery and take out the negative electrode. Soak the negative electrode in DMC for 24 hours and then dry it to obtain the negative electrode required for testing.

[0096] Sampling test: Cut the negative electrode sheet to be tested into 30mm diameter discs, cut 10 pieces, and test according to the following method to obtain 10 sets of data. The average value of the 10 sets of data is the thermal resistance R of the sample.

[0097] Use the Hot Disk thermal constant analyzer and install the Hot Disk probe on the pole piece to ensure good contact between the probe and the pole piece. Start the test equipment, heat the probe to generate heat, and the heat diffuses through the sample under test. The test equipment monitors the temperature change of the probe in real time and records the temperature change curve over time. When the probe reaches a stable state, the test equipment automatically stops heating and starts the cooling process, and also records the temperature change curve of the probe during the cooling process. According to the temperature change curve recorded by the test equipment, the thermal resistance R of the sample is calculated using professional data analysis software.

[0098] 3. Powder porosity test

[0099] The test was conducted using the AutoPore V fully automatic mercury intrusion pore size analyzer from Micromeritics. The specific test method is as follows:

[0100] First, place the graphite in a vacuum oven and dry it in vacuum at 110℃ for 1h. Use an analytical balance to accurately weigh the weight of the dried graphite sample. Load the weighed graphite sample into the head of a 15ml powder dilatometer and apply vacuum sealing ester to seal it. Use an analytical balance to weigh the weight of the dilatometer assembly loaded with the sample again. Install the dilatometer loaded with the sample on the low-pressure station of the mercury intrusion meter, perform low-pressure analysis, and record and analyze relevant data. After the low-pressure analysis is completed, transfer the dilatometer to the high-pressure chamber, seal the high-pressure chamber, and perform high-pressure analysis. After the analysis is completed, obtain the porosity test data from the instrument and display it on the computer screen.

[0101] 4. Particle size test

[0102] The particle size distribution ranges of the first graphite material, the second graphite material and the ternary material were tested by a Malvern laser particle size analyzer, and the particle size Dv50 corresponding to 50% of the particle size volume distribution of the material was regarded as the median particle size of the material.

[0103] 5. First Coulomb efficiency test

[0104] (1) Battery disassembly and negative electrode sheet acquisition: Safely disassemble the battery in a fully discharged (empty) state and remove the negative electrode sheet;

[0105] (2) Paste layer processing: Use a plastic scraper to gently scrape off the paste layer on the negative electrode sheet, collect the scraped paste layer, and prepare for subsequent processing.

[0106] (3) Ultrasonic treatment and filtration: The scraped paste layer was placed in a DMC solvent and subjected to ultrasonic treatment for 2 hours to wash away the organic SEI film and residual lithium salt.

[0107] (4) Pickling treatment: The cleaned negative electrode material is placed in a hydrochloric acid solution and soaked for 2 hours for pickling treatment. The purpose of pickling is to remove the inorganic SEI film on the negative electrode material.

[0108] (5) Cleaning and drying: Use deionized water to clean the negative electrode material after acid washing several times to completely remove the residual hydrochloric acid and other impurities. After cleaning, place the negative electrode material in a drying device for drying until it is completely dry.

[0109] (6) Button cell production: The processed negative electrode material is assembled with other necessary battery components (such as positive electrode, separator, electrolyte, etc.) into a button cell.

[0110] (7) Charge and discharge test and coulomb efficiency calculation: Perform a complete charge and discharge cycle test on the manufactured button cell. Record the discharge capacity and charge capacity, and calculate the ratio of discharge capacity to charge capacity, that is, the first coulomb efficiency after the negative electrode material is formed.

[0111] 6. Compaction density test

[0112] (1) Soak the negative electrode sheet in deionized water, remove the paste layer to obtain the current collector, cut the current collector into small discs with a diameter of 10 mm, randomly cut 10 pieces, calculate the surface density of 10 pieces of small discs to obtain the surface density Q1 of the current collector, surface density = mass / area;

[0113] (2) Paste surface density test: 10 pieces of small discs with a diameter of 10 mm were randomly cut and weighed. The surface density Q2 containing the current collector was calculated using the formula surface density = mass / area. (Q2-Q1) / 2 is the surface density of the single-sided paste layer.

[0114] (3) Calculation of compaction density: Use a caliper to measure the thickness of the current collector h1 and the thickness of the paste layer containing the current collector h2. (h2-h1) / 2 is the thickness of the single-sided paste layer. The compaction density T = {(Q2-Q1) / 2} / {(h2-h1) / 2}.

[0115] 7. Lithium ion solid phase diffusion coefficient test

[0116] (1) The positive and negative electrode active material powders are assembled into a button battery according to the mass ratio of active material, conductive carbon black, binder CMC, and SBR being 96:2:1:1.

[0117] (2) Tested using the Xinwei charge and discharge test software BTS: 3 charge and discharge cycles were performed at a current of 0.05C to activate the positive and negative electrode materials. After 3 charge and discharge cycles, the positive electrode material was discharged to 2.8V and the negative electrode material was charged to 1.5V. The upper and lower limit voltages of the positive electrode material were 4.3V and 2.8V respectively; the upper and lower limit voltages of the negative electrode material were 1.5V and 0.01V respectively.

[0118] (3) Use the constant current intermittent titration technique (GITT) to test the diffusion coefficients of the positive and negative electrode materials. The positive electrode material is tested for the diffusion coefficient of the charging process (positive electrode material lithium insertion), and the negative electrode material is tested for the diffusion coefficient of the discharge process (negative electrode material lithium removal). The specific steps are as follows:

[0119] For positive electrode materials, ① 0.05C constant current charging for 30 minutes, set aside for 120 minutes, ② continue step ① until the battery voltage is charged to 4.3V; for negative electrode materials, ① 0.05C constant current discharge for 30 minutes, set aside for 120 minutes, ② continue step ① until the battery voltage is discharged to 0.01V. After setting the process steps according to the above steps, click Start to perform the GITT test. After the test is completed, click the D tool in the test software menu bar, then click the GITT button, enter the relevant parameters, and then perform diffusion coefficient analysis and calculation according to the following company. The formula is Where: τ is the relaxation time, m B is the mass of active material, M B is the molar mass of the active material, V M is the molar volume, S is the electrode / electrolyte contact area, ΔE s is the total voltage change caused by the pulse, ΔE t It is the voltage change of constant current charge / discharge.

[0120] 8. Battery capacity, thickness and energy density test

[0121] At 25°C, the prepared finished battery was charged at a constant current and constant voltage of 0.2C to a full charge of 4.3V, the current was cut off at 0.05C, and then discharged at 0.2C to 3V. The discharged capacity was recorded as the battery capacity.

[0122] The prepared finished battery was charged to 30% SOC at 0.2C at 25°C, and the battery thickness was tested using 600g PPG.

[0123] Calculate volume energy density = battery capacity * platform voltage / battery length / width / thickness.

[0124] 9. Low temperature discharge test

[0125] The prepared finished battery was charged to 20% SOC at a current of 0.5C at 25°C, placed at 0°C for 4 hours, and then discharged to 3V at a current of 1C, and the discharged capacity was recorded.

[0126] 10. Cycle test

[0127] The prepared finished battery was charged at 3C constant current and constant voltage at 25°C to a full charge of 4.3V, the current was cut off at 0.05C, and it was discharged to 3V at 1C. This was considered a charge and discharge cycle. After 1000 cycles, the battery capacity retention rate and expansion rate were confirmed.

[0128] The above test results are shown in Tables 1-4 and Figure 3 As shown. Among them, A1 is the first active layer at 4000-2000cm -1Infrared absorption rate in the range of 4000-2000cm -1 The infrared absorption rate within the range, R1 is the thermal resistance of the first region, R2 is the thermal resistance of the second region, η1 is the first coulomb efficiency of the first active layer, η2 is the first coulomb efficiency of the second active layer, and H=η1 / η2.

[0129] Table 3

[0130]

[0131]

[0132] Table 4

[0133]

[0134]

[0135] It can be seen from Tables 1 to 4 that the lithium-ion secondary batteries prepared in Examples 1 to 29 exhibit excellent low-temperature discharge capability and cycle performance while maintaining a relatively high energy density. This indicates that appropriately increasing the infrared absorption rate of the middle region of the negative electrode sheet can improve the heat preservation effect of the region, thereby significantly improving the low-temperature discharge capability of the battery.

[0136] Compared with Example 1, the A1 / A2 value of Comparative Example 2 is too large, and the A1 value of Comparative Example 5 is too large, which is beneficial to improving the low-temperature discharge capacity of the battery, but will lead to a decrease in energy density and affect the cycle performance. On the contrary, Comparative Example 1 only uses graphite with small porosity, the A1 value of Comparative Example 4 is too small, and the A1 / A2 value of Comparative Example 3 is too small, which has no substantial effect on improving the low-temperature discharge capacity of the battery.

[0137] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.

Claims

1. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active layer disposed on at least one side surface of the negative electrode current collector in a thickness direction; characterized in that: In the first direction, the negative electrode active layer comprises a first active layer (1) and a second active layer (2) adjacent to each other, and the second active layer (2) is located at one end or both ends of the first active layer (1) in the first direction; The first active layer (1) has a surface area of ​​4000-2000 cm -1 The infrared absorption rate in the range of 4000-2000cm is recorded as A1, and the second active layer (2) has an infrared absorption rate of 4000-2000cm -1 The infrared absorption rate within the range is recorded as A2, and A1 and A2 satisfy: 1.25≤A1 / A2≤2.25, and 75%≤A1≤90%.

2. The negative electrode sheet according to claim 1, characterized in that: 40%≤A2≤60%; And / or, in the first direction, the width of the first active layer (1) is W1, 50 mm ≤ W1 ≤ 160 mm; the width of the second active layer (2) is W2, W1 and W2 satisfy: W2 = (1 / 6 - 1 / 3) * W1.

3. The negative electrode sheet according to claim 1, characterized in that: The compaction density T1 of the first active layer (1) and the compaction density T2 of the second active layer (2) satisfy: T1 = (0.9-1) * T2, 1.4 g / cm 3 ≤T2≤1.6g / cm 3 ; And / or, the negative electrode sheet comprises a plurality of electrode tabs (3), and the plurality of electrode tabs (3) are arranged in sequence along the length direction of the negative electrode sheet.

4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The negative electrode sheet comprises a first region and a second region, the first region comprises the first active layer (1), and the second region comprises the second active layer (2); The thermal resistance R1 of the first region and the thermal resistance R2 of the second region satisfy: 2≤R1 / R2≤5, and 0.1mK / W≤R1≤0.125mK / W, 0.025mK / W≤R2≤0.05mK / W.

5. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The first active layer (1) comprises a first graphite material, wherein the first graphite material satisfies: a graphitization degree ≥ 0.93, a porosity P1 of 10%-40%, a median particle size G1 of 7 μm-11 μm, and a specific surface area S1 of 3 m 2 / g-6m 2 / g; And / or, the second active layer (2) comprises a second graphite material, wherein the second graphite material satisfies: a graphitization degree ≥ 0.93, a porosity P2 of 1%-5%, a median particle size G2 of 7 μm-11 μm, and a specific surface area S2 of 1 m 2 / g-2m 2 / g.

6. The negative electrode sheet according to claim 5, characterized in that: The first coulombic efficiency η1 of the first active layer and the first coulombic efficiency η2 of the second active layer satisfy the following: H=η1 / η2, 0.90≤H≤0.99, 85%≤η1≤91%, 92%≤η2≤94%.

7. A lithium ion secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet as claimed in any one of claims 1 to 6, and an electrolyte.

8. The lithium ion secondary battery according to claim 7, characterized in that: The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer disposed on at least one side surface of the positive electrode current collector in the thickness direction, the positive electrode active layer includes a ternary material, the median particle size G3 of the ternary material is 2 μm-6 μm, and the chemical formula of the ternary material is LiNi x Co y Mn z O2, where x+y+z=1, 0.6≤x<1, 0<y<0.2, 0<z<0.

2.

9. The lithium ion secondary battery according to claim 8, characterized in that: The lithium ion solid phase diffusion coefficient D1 of the ternary material is 3×10 -12 cm 2 / s-2.5×10 -10 cm 2 / s, the lithium ion solid phase diffusion coefficient D2 of the first graphite material is 4.0×10 -12 cm 2 / s-2.0×10 -9 cm 2 / s, and D1 and D2 satisfy: C = (lgD1) / (lgD2), 0.84≤C≤1.

32.

10. The lithium ion secondary battery according to any one of claims 7 to 9, characterized in that: The electrolyte comprises an organic solvent and an electrolyte and an additive dissolved in the organic solvent, wherein the organic solvent comprises ethylene carbonate, ethyl methyl carbonate and methyl acetate, and the content of methyl acetate is 15%-30% based on the mass of the electrolyte; And / or, the additive includes fluoroethylene carbonate and / or lithium difluorophosphate, and based on the mass of the electrolyte, the content of the fluoroethylene carbonate is 2%-10%, and the content of the lithium difluorophosphate is 0.5%-3.5%; Preferably, the content of the fluoroethylene carbonate is 3%-5%; Preferably, the content of lithium difluorophosphate is 1%-2.5%.